Older Women's Expectations of Care, Reciprocity, and Government Support in Australia. 'Am I Not Worthy?'. Issue 3 (3rd July 2018) - Curryer, Cassie; Gray, Mel; Byles, Julie E.
ABSTRACT: This paper considers the lived experience and meaning of care for women born between 1946 and 1951, who are living alone, and are participants in the Australian Longitudinal Study of Women's Health (ALSWH). The discussion is based on free-text survey comments ( n = 150 women) and in-depth interview data ( n = 15 women) exploring women's experiences of ageing and their future expectations of care. It delves into tensions within relevant themes relating to care (unpaid informal care, volunteer work, and reciprocity), and the caring ethos, as described by women who are ageing in Australian communities. It highlights dilemmas faced by women who have grown old with the expectation of government support and care in later life, but who are facing the possibility this might not eventuate. These dilemmas are discussed with reference to governmental ethical-moral responsibilities for care within the context of user-pays welfare systems and profiteering within marketised aged-care services.